1998
DOI: 10.1002/jor.1100160604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 25‐OH‐vitamin D on fracture healing in elderly rats

Abstract: To investigate the effect of 25-OH-vitamin D supplements (calcidiol) on fracture healing in the elderly, an experimental model with 15 18-month-old female Wistar rats was designed. An experimental fracture in the middle third of both femora of each rat was made. Then the rats were randomly assigned to two groups: one group was subcutaneously treated with 25-OH-vitamin D during all healing processes, and the other group (the control group) was not. After 5 weeks of healing, the animals were killed and both femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 12 publications
1
54
0
5
Order By: Relevance
“…In addition to its effect on calcium and phosphate homeostasis, Vitamin D has an effect on bone healing and remodelling through upregulation of osteoblast activity, and stimulation of osteoclastogenesis [25]. Animal studies have shown improved rates of fracture healing with vitamin D supplementation [26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its effect on calcium and phosphate homeostasis, Vitamin D has an effect on bone healing and remodelling through upregulation of osteoblast activity, and stimulation of osteoclastogenesis [25]. Animal studies have shown improved rates of fracture healing with vitamin D supplementation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Hypovitaminosis-D may predispose bone to stress fractures by decreasing tolerance to structural overload and by complicating recovery in certain individuals 7. We present a case which highlights the need to consider hypovitaminosis-D when investigating background causation and treatment of femoral and tibial stress fracture.…”
Section: Introductionmentioning
confidence: 91%
“…Most animal studies examining the role of vitamin D have shown a positive effect on fracture healing [11][12][13][14]. In animal models, the plasma concentration of 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), one of the active vitamin D metabolites, rapidly decreases following a fracture.…”
Section: Animal Studiesmentioning
confidence: 99%